2012
DOI: 10.1038/jcbfm.2012.87
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Functional Cerebral Blood Volume Responses to Normobaric Hyperoxia in Acute Ischemic Stroke

Abstract: Studies suggest that neuroprotective effects of normobaric oxygen (NBO) therapy in acute stroke are partly mediated by hemodynamic alterations. We investigated cerebral hemodynamic effects of repeated NBO exposures. Serial magnetic resonance imaging (MRI) was performed in Wistar rats subjected to focal ischemic stroke. Normobaric oxygen-induced functional cerebral blood volume (fCBV) responses were analyzed. All rats had diffusion-weighted MRI (DWI) lesions within larger perfusion deficits, with DWI lesion exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…As HBO requires a chamber or other equipment to create a hyperbaric atmosphere, NBO is simple to administer, inexpensive and can be started by paramedics after stroke onset en route to a hospital. NBO reduced ischemic brain injury and improved functional outcome in several animal models (Singhal et al , 2002a; Liu et al , 2006; Henninger et al , 2007; Yuan et al , 2010; Wu et al , 2012). The neuroprotective effects of NBO may be explained by many possible mechanisms, such as improved metabolism, reduced oxidative stress, and preservation of the BBB.…”
Section: Medical Gasesmentioning
confidence: 99%
See 1 more Smart Citation
“…As HBO requires a chamber or other equipment to create a hyperbaric atmosphere, NBO is simple to administer, inexpensive and can be started by paramedics after stroke onset en route to a hospital. NBO reduced ischemic brain injury and improved functional outcome in several animal models (Singhal et al , 2002a; Liu et al , 2006; Henninger et al , 2007; Yuan et al , 2010; Wu et al , 2012). The neuroprotective effects of NBO may be explained by many possible mechanisms, such as improved metabolism, reduced oxidative stress, and preservation of the BBB.…”
Section: Medical Gasesmentioning
confidence: 99%
“…NBO has been shown to induce vasoconstriction and improve dynamic functional cerebral blood flow in salvageable tissue (Wu et al , 2012), as well as increasing O2 availability, reducing metabolic disturbances and protecting the blood brain barrier (Shin et al , 2007; Liu et al , 2011a). In addition, it is simple to administer, noninvasive, inexpensive, widely available, and can be started promptly after stroke onset.…”
Section: Medical Gasesmentioning
confidence: 99%
“…7 Several animal studies have shown that short duration of NBO treatment is highly neuroprotective if started early after ischemia onset. 8-12 A pilot clinical study also demonstrated that NBO therapy was associated with a transient improvement of clinical deficits and magnetic resonance imaging abnormalities in patients with acute ischemic stroke. 13 These studies have demonstrated that early NBO treatment can slow the progression of ischemic brain tissue to necrosis, thus improving the therapeutic time window for reperfusion therapies.…”
Section: Introductionmentioning
confidence: 99%
“…A study using functional cerebral blood volume (fCBV) also showed that contralateral healthy tissue responded consistently with vasoconstriction (fCBV reduction), while tissue from ischemic core showed marginal fCBV changes that later became moderate fCBV reductions. As for penumbra tissue, it showed relative preservation of mean fCBV at early time points, later exhibited significantly decreased fCBV (vasoconstriction) like healthy tissue [16]. …”
Section: Nbo-afforded Neuroprotection In Strokementioning
confidence: 99%